PC.61 Therapeutic Hypothermia – an evaluation of a two network education programme. (9th June 2014) - Philpott, A; Clarke, L; Cookson, J
Abstract : Background: Therapeutic Hypothermia (TH) improves neurological outcomes for a selected neonatal population. The need for on-going education in commencing TH was recognised by the Southern West Midlands (SWM), Staffordshire, Shropshire and Black Country (SSBC) Neonatal Networks and their neonatal transport team (WMNTS). The first of four study days was designed and delivered in June 2012. Aims: To report feedback on the network study days To evaluate change in practice (2009–2013). Data collection: Study day evaluation formsInformation taken from WMNTS database Results staff feedback: 86% of staff reported the study day was highly relevant to their needs; 100% would change clinical practice; 77% marked the programme as excellent. Improvements in provision of TH commenced prior to the network study days and may be due to additional factors. Not all transfers and staff opinions may have been captured. Conclusion: From 2009–2013 we have reported an increase in the number of babies being referred for TH; in 2013 the average temperature on arrival of the transport team is within the TH range and the time to achieve TH remains below the desired 6 h target. Future developments: The day will repeat in May 2013 in response to local demand. Reference: Jacobs SE, et al . Cooling for newborns with neonatal encephalopathy. Cochrane Database of Systematic Reviews 2013, Issue 1